Valorização de resíduos de seringueira: obtenção por via mecânica de nanofibrilas de celulose e aplicação em látex de borracha natural - Evangelista, Natalia Cristina (Universidade Federal de São Carlos, 2025)
Waste generation and environmental pollution are currently the focus of much research today. In the cultivation of rubber trees for the production of natural rubber, for example, after years of exploitation, the trees are cut down, generating large quantities of wood, which during processing generate a high volume of waste. In this context, this research project aimed to obtain porous nanocomposites from natural rubber latex and cellulose nanofibrils (CNFs) obtained mechanically (defibrillator mill) from rubber tree waste, using sodium bicarbonate as a blowing agent, aiming to remove contaminants from aquatic environments. The fibers were chemically treated to remove lignin and hemicellulose, in order to evaluate the influence of these components on the mechanical defibrillation process. The resulting cellulose suspensions showed high yield (91.5%, 81.4% and 85.0%), and the one with the highest colloidal stability (zeta potential = -32.6 mV) contains the lowest lignin content (5.9%). The porous nanocomposites containing 3% NaHCO3 and 1% CNF showed higher compressive strength (TS ~ 6.2 MPa) without significant changes in elasticity. Furthermore, the surface hydroxyl groups of CNFs influenced the increase in the water absorption capacity of the nanocomposites. This study showed a promising strategy for the valorization of rubber wood residues, which, after processing, are converted into cellulose nanofibrils (CNFs) that, when applied to natural rubber latex, result in porous composite materials.
Valorization of rubber tree waste: mechanical production of cellulose nanofibrils and their application in natural rubber latex
Keywords: Resíduos madeireiros; Fibra vegetal; Desfibrilação mecânica; Nanofibrilas de celulose; Borracha natural; Materiais porosos; Agente de expansão; Wood waste; Vegetable fiber; Mechanical defibrillation; Cellulose nanofibrils; Natural rubber; Porous materials; Blowing agent; CIENCIAS EXATAS E DA TERRA::QUIMICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA; 9. Indústria, Inovação e Infraestrutura; 12. Consumo e Produção Responsáveis